KONSELING KELOMPOK PADA SISWA MTs DARUL ABROR KEDUNGJATI BUKATEJA PURBALINGGA: APAKAH BERPENGARUH TERHADAP MOTIVASI BELAJAR SISWA? [GROUP COUNSELING OF STUDENTS AT MTs DARUL ABROR KEDUNGJATI BUKATEJA PURBALINGGA: DOES IT AFFECT STUDENT LEARNING MOTIVATION?] - Mala, Muhammad Yusuf; Isnaeni, Subi Nur (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2023)
This study aims to determine how much influence group counseling has on students' motivation to learn. The method used in this study was a pre-experimental design with a one-group pre-test post-test design. The sample or respondents in this study were 12 students at MTs Darul Abror Kedungjati Bukateja Purbalingga. Data collection techniques used in this study are using questionnaires and observation. The data analysis technique used in this study is the paired t-test. The results obtained are that there is an influence between group counseling and learning motivation. Where is the paired t-test on the basis of decision making paired t-test if the sig (2-tailed) is less than 0.05, then there is an influence between the pre-test and post-test data. In addition, the results obtained by the t-count are -16,150 so that it can be concluded that there is an influence between the variables X and Y. The results of this study can be useful for educators in the world of education to pay more attention to students in providing learning motivation to students.